Removal of Copper from Batik Liquid Waste using Lignite - Wahyu Wilopo, Wahyu Wilopo (2013)
Industrial development and urbanization do not only increase economic growth but also contribute to environmental degradation, such as water contamination. Batik industry is one of domestic industries in Yogyakarta Province which produce a liquid waste containing copper (Cu2+). The concentration of copper in liquid waste has been found to be much higher than that WHO standard. The liquid waste produced in batik industry is commonly discharged directly to the rivers without any treatment, causing a serious environmental issue. lignite is one of many geological materials which have potential to absorb heavy metals. It is cheap and available locally, such as in Kulonprogo, one of districts in Yogyakarta. However, the potential application of lignite for increasing of community prosperity has not been investigated properly due to the low calorie value. The purpose of this study was to investigate the capability of lignite obtained from Kulonprogo to reduce Cu2+ in batik waste contaminated water and to understand the ion removal mechanism by conducting batch and column experiments. The results showed that Cu2+ ions in contaminated water samples decreased significantly due to complexation and cations exchange. This confirms teh potential use of lignite as a cost-effective material for treatment of liquid waste generated in Batik industry.